Evolution of ultrafine precipitates and its influence on wear mechanism in cryoprocessed high nitrogen martensitic steel. (2nd October 2019) - Upadhye, A. P.; Shah, N.; Lalge, P.; Dhokey, N. B.; Tharian, T.
ABSTRACT: Development of the space engines with liquid propellants necessitates the use of bearings of high quality. During recent years, a new family of high strength corrosion resistant steels, with partial replacement of carbon by nitrogen, known as high nitrogen steels were developed having higher impact strength and fracture toughness coupled with high hardness for antifriction bearing of cryopumps in rocket. In this research work, wear characteristics of cryogenically treated high nitrogen martensitic stainless steels were investigated by Pin-on-disc wear testing machine. After conventional hardening treatment, specimens were subjected to cryogenic treatment at −196°C with cryosoaking period varying from 8 to 32 h in the interval of 8 h followed by soft tempering. These specimens were analysed for hardness, wear resistance, subsurface and worn surface features by SEM. It is established that there is a profound influence of nucleation and growth of precipitates on the wear behaviour and the underlying wear mechanisms.